Preparation and characterization of 4-isopropylcalix[4]arene-capped (3-(2-O-β-cyclodextrin)-2-hydroxypropoxy)-propylsilyl-appended silica particles as chiral stationary phase for high-performance liquid chromatography - Chelvi, S.K.T. (2014)
10.1016/j.chroma.2013.11.025